ALGORITHM FOR DETERMINATION OF PREDICTABLE SPECIALISTS’ NUMBER REQUIRED FOR STAFF RECRUITMENT AT ENTERPRISE - V. P. Goncharenko; D. N. Mironov; I. A. Rizhаnkov (Наука и техника)
A methodology has been developed which allows to calculate predictable enterprise requirements for skilled staff with the purpose to ensure a normal functioning of its production process and also to determine changes of its staff structure in case of the production development and usage of innovations in production.